Influential Article Review -The Intermediary Duties of Value Congruence and Leader-Member Exchange (Journal of Leadership, Accountability and Ethics, 2019)
This paper examines leadership. We present insights from a highly influential paper. Here are the highlights from this paper: Limited empirical investigation has been devoted to understanding the multiple- effect mechanisms of moral leadership, especially the relationship between mediators. Drawing from both social learning and social exchange theories, this study examines whether value congruence and leader-member exchange (LMX) mediate the effect of moral leadership on followers’ positive work behaviors. Using two-wave survey data from 395 Chinese employees, the results indicate that both value congruence and LMX act as mediators in the relationship between moral leadership and positive work behaviors. Furthermore, a sequential mediation link from moral leadership to value congruence, then to LMX, and finally to positive work behaviors was established. Theoretical and practical implications are further discussed. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.
Keywords: Moral leadership; Value congruence; Leader-member exchange (LMX); Positive work behaviors; Social learning; Social exchange